Maternal Predictors of Blood Transfusion among Neonates in the Neonatal Intensive Care Unit of Ahmadu Bello University Teaching Hospital Zaria, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Maternal health and healthcare accessibility are important determinants of neonatal survival. Pregnancy-related complications may lead to maternal anemia and, maternal micronutrient deficiency, conditions which could result in neonatal anemia necessitating transfusion.Objectives:To determine maternal predictors of neonatal blood transfusion.Methods:We conducted a case–control study on mother–infant pairs of cases and controls. A semi-structured questionnaire was used to collect information. Logistic regression was used on maternal predictors, and the level of significance was set at ≤0.05.Results:The overall mean (±standard deviation) age of mothers in both case and control groups was 21.79 ± 10.71 years, respectively. The likelihood of neonatal transfusion was increased by parity of ≥5 [odds ratio (OR): 3.1, 95% confidence interval (CI) = 1.26–7.39], while age of ≥18 years at first marriage, attainment of at least secondary school, four antenatal care (ANC) visits before delivery, birth interval of ≥2 years, and hematinics use during pregnancy were associated with reduced neonatal blood transfusion (OR: 0.36, 95% CI = 0.14–0.96), (OR: 0.66, 95% CI = 0.32–1.37), (OR: 0.70, 95% CI = 0.25–1.99), (OR: 0.55, 95% CI = 0.19–1.62), and (OR: 0.63, 95% CI = 0.17–2.36), respectively.Conclusion:We found that high parity, teenage mothers, inadequate ANC visits, short birth interval, and hematinics noncompliance during pregnancy were all associated with increased need of blood transfusion among neonates.